ACUTE TOXICITY TEST OF ETHANOLIC EXTRACT OF Acalypha hispida LEAVES IN FEMALE RATS: A PHYSIOLOGICAL AND HISTOLOGICAL STUDY - Alfarisi, Hamzah; Subangkit, Mawar; Sadiah, Siti; Wresdiyati, Tutik (Jurnal Kedokteran Hewan, 2020)
This research aims to evaluate the safety of ethanolic extract of Acalypha hispida (A. hispida) leaves with acute toxicity test using 15 female rats strain Sprague-Dawley. A single dose of different doses of extract (2, 4, 8, and 16 g/kg body weight) was administrated orally, and theobservation was conducted for 14 days. The results revealed that the ethanolic extract of A. hispida leaves was relatively harmless (LD50 16 g/kg BW), did not affect body weight, and did not show clinical signs of toxicity during the observation periods. The parameters of blood serumbiochemistry of all extract-treated groups (alanine aminotransferase, aspartate aminotransferase, creatinine, and urea) did not change significantly compared to the control group. The histological observation of the liver showed a significant increase in eosinophilic cytoplasm and basophilic nuclei at all doses. However, the ethanolic extract of A. hispida leaves did not significantly affect glomerulus/Bowmans capsule ratio, glomerular cell density, and the proportion of normal cell tubule. In conclusion, the ethanolic extract of A. hispida leaves was relatively harmless with LD5016 g/kg BW and seems to be safe in low doses (2 g/kg BW).